Dehydroepiandrosterone (DHEA) prevents and reverses chronic hypoxic pulmonary hypertension - Bonnet, Sébastien (National Academy of Sciences, 2003)
Pulmonary artery (PA) hypertension was studied in a chronic hypoxic-pulmonary hypertension model (7–21 days) in the rat. Increase in PA pressure (measured by catheterism), cardiac right ventricle hypertrophy (determined by echocardiography), and PA remodeling (evaluated by histology) were almost entirely prevented after oral dehydroepiandrosterone (DHEA) administration (30 mg/kg every alternate day). Furthermore, in hypertensive rats, oral administration, or intravascular injection (into the jugular vein) of DHEA rapidly decreased PA hypertension. In PA smooth muscle cells, DHEA reduced the level of intracellular calcium (measured by microspectrofluorimetry). The effect of DHEA appears to involve a large conductance Ca(2+)-activated potassium channel (BK(Ca))-dependent stimulatory mechanism, at both function and expression levels (isometric contraction and Western blot), via a redox-dependent pathway. Voltage-gated potassium (Kv) channels also may be involved because the antagonist 4-amino-pyridine blocked part of the DHEA effect. The possible pathophysiological and therapeutic significance of the results is discussed.